Analytical and Experimental Optimization of Nylon Weave Woven Fabrics with Polyester Composite Thick Plates - Faidh - Allah, Majid H. (Nahrain University College of Engineering Journal, 2012)
The study in present paper deals with find the analytical and experimental for optimum of thick composite plate made of nylon weave woven fabrics with polyester (ply angle and stacking sequences) with two optimization strategy (linear programming LP and genetic algorithm GA) for simply supported thick plate with central point load condition tacking in consideration the price and weight of materials in used. A simulation program build with MATLAB to find out the optimum design and finally compare the results using ANSYS then for check the manufacturing quality of plates, the first natural frequencies of prepared plates and ANSYS model is compared.From this paper results, the maximum difference between the LP and GA optimization with displacement ANSYS results are 5% and 7% respectively, and the maximum difference between the experimental and ANSYS of the first natural frequency results are 18% and 19% LP and GA results respectively.